Effect of Growth Hormone on Orthodontic Tooth Movement: A Review: Effect of Growth Hormone on Orthodontic Tooth Movement: A Review - Kadhom, Zainab M.; Al-mashhadany, Sara M.; Hassan, Alaa F. A.; Hassan, Alaa F. A. (Scientific Journal of Medical Research, 2022)
Objectives: The purpose of the present review is to look into the impact of growth hormone on orthodontic tooth movement. Sources and Data: To search for orthodontic treatment in elderly patients, a literature review of English papers was undertaken using Google Scholar, PubMed, and Scopus. Conclusion: Growth hormones have a great importance in the growth of the face and craniofacial structures, also they affect tooth movement during orthodontic treatment, so orthodontists must have a background of knowledge about these hormones and their impact on the movement of the teeth before starting treatment because any defect in these hormones may negatively affect orthodontic treatment